2020
DOI: 10.3389/fnagi.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Sirtuin 2 in Parkinson’s Disease

Abstract: Parkinson's disease (PD), the main risk factor of which is age, is one of the most common neurodegenerative diseases, thus presenting a substantial burden on the health of affected individuals as well as an economic burden. Sirtuin 2 (SIRT2), a subtype in the family of sirtuins, belongs to class III histone deacetylases (HDACs). It is known that SIRT2 levels increase with aging, and a growing body of evidence has been accumulating, showing that the activity of SIRT2 mediates various processes involved in PD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 131 publications
(163 reference statements)
0
41
1
2
Order By: Relevance
“…Based on previous findings of SIRT2 over-expression inducing dopaminergic cell death while enzyme inhibition exerting neuroprotective effects, it was concluded that elevated SIRT2 levels contribute to higher PD risk. In contrast to previous studies reporting on SIRT2 effects on microtubule stability, formation of alpha-synuclein aggregation, neuroinflammation and autophagy 39 our results do not support the role of SIRT2 in PD.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on previous findings of SIRT2 over-expression inducing dopaminergic cell death while enzyme inhibition exerting neuroprotective effects, it was concluded that elevated SIRT2 levels contribute to higher PD risk. In contrast to previous studies reporting on SIRT2 effects on microtubule stability, formation of alpha-synuclein aggregation, neuroinflammation and autophagy 39 our results do not support the role of SIRT2 in PD.…”
Section: Discussioncontrasting
confidence: 99%
“…PD not only does reduce the patient's quality of life but also brings a heavy economic burden to society and families ( 49 , 50 ). Balance dysfunction is the main reason for the increase in individuals' disability rates with PD and the decreased health-related quality of life and survival ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT2 has been reported to mediate α-Syn protein aggregation which also induces oxidative stress, in turn, leading to PD pathogenesis ( de Oliveira et al, 2017 ; Liu et al, 2020 ; Singh et al, 2017b ). SIRT2 by deacetylating FOXO3a has been shown to increase antioxidant defense mechanisms.…”
Section: Sirt1 and Sirt2 In Parkinson’s Diseasementioning
confidence: 99%